Current Devices and Complications Related to Transcatheter Mitral Valve Replacement: The Bumpy Road to the Top - Kargoli, Faraj; Pagnesi, Matteo; Rahgozar, Kusha; Goldberg, Ythan; Ho, Edwin; Chau, Mei; Colombo, Antonio; Latib, Azeem (Frontiers in Cardiovascular Medicine, 2021)
Mitral regurgitation is the most common valvular lesion in the developed world, with increasing prevalence, morbidity, and mortality. The experience with surgical mitral valve repair or replacement is very well validated. However, more than 45% of these patients get denied surgery due to elevated risk profile and the advanced disease of the left ventricle at time of presentation, promoting the need for less invasive transcatheter options such as transcatheter repair and transcatheter mitral valve replacement (TMVR). Early available TMVR studies have shown promising results, and several dedicated devices are under clinical evaluation. However, TMVR is still in the early developmental stages, and is associated with a non-negligible risk of peri- and post-procedural complications. In this review, we discuss the current challenges facing TMVR and the potential TMVR-related complications, offering an overview on the measures implemented to mitigate these complications, and future implications.